2019
DOI: 10.1002/htj.21554
|View full text |Cite
|
Sign up to set email alerts
|

Steady incompressible magnetohydrodynamics Casson boundary layer flow past a permeable vertical and exponentially shrinking sheet: A stability analysis

Abstract: Steady incompressible magnetohydrodynamic mixed convection boundary layer flow of a Casson fluid on an exponentially vertical shrinking sheet using the non-Newtonian heating equation is investigated in this paper. There are three main objectives of this study, namely, to develop a new mathematical model, to obtain multiple solutions, and to perform stability analysis. The governing partial differential equations have been changed into nonlinear ordinary differential equations. The resultant equations of bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 38 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…According to Lund et al [37], in order to assess the stability of Equations (21)- (24) we need to relax one boundary condition on F 0 (η), G 0 (η), or H 0 (η). It should be noted that we relaxed F 0 (η) → 0 as η → ∞ to F 0 (0) = 1 in this problem.…”
Section: Stability Analysismentioning
confidence: 99%
“…According to Lund et al [37], in order to assess the stability of Equations (21)- (24) we need to relax one boundary condition on F 0 (η), G 0 (η), or H 0 (η). It should be noted that we relaxed F 0 (η) → 0 as η → ∞ to F 0 (0) = 1 in this problem.…”
Section: Stability Analysismentioning
confidence: 99%
“…According to Weidman et al [49] and Lund et al [50], the existence of multiple solutions is possible in fluid flow problems in some ranges of physical parameters. It is necessary to carry out stability analysis in order to determine which one solution is stable.…”
Section: Stability Analysismentioning
confidence: 99%
“…Rasool et al [6,7] reported on some interesting findings in Marangoni convection of nanofluids involving simple as well as Riga plates with various other important physical parameters, respectively. Some recent and interesting articles can be found in [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and cross references cited therein.…”
Section: Introductionmentioning
confidence: 99%